Synthesis of Some New Anils: Part 1. Reaction of 2-Hydroxy-benzaldehyde and 2-Hydroxynaphthaldehyde with 2-Aminopyridene and 2-Aminopyrazine - Khadija O. Badahdah; Abdullah M. Asiri (Molecules, 2007)
New Schiff bases derived from 2-aminopyridene and 2-aminopyrazine have been synthesized. The UV-Visible spectra of the compounds have been investigated in acetonitrile and toluene. The compounds were in tautomeric equilibrium (enol-imine O– H···N, keto-amine O···H–N forms) in polar and nonpolar solvents. For some derivatives the keto-amine form was observed in both toluene and acetonitrile. 1H-NMR and IR results showed that all Schiff bases studied favor the enol-imine form over the keto form in a weakly polar solvent such as deuterochloroform.